Fatty Acid Content of Four Salmonid Fish Consumed by Indigenous Peoples from the Yamal-Nenets Autonomous Okrug (Northwestern Siberia, Russia) - Alexander G. Dvoretsky; Fatima A. Bichkaeva; Olga S. Vlasova; Sergei V. Andronov; Vladimir G. Dvoretsky (Animals, 2022)
We assayed fatty acids in the flesh of Arctic cisco Coregonus autumnalis (adult and juvenile), least cisco Coregonus sardinella, muksun Coregonus muksun, and Arctic charr Salvelinus alpinus inhabiting water bodies of the Gydan Peninsula, Siberia, Russia. The highest concentrations of total and polyunsaturated fatty acids (PUFAs) were found in Arctic charr (27.8 and 9.5 mg g−1) and adult Arctic cisco (20.2 and 7.6 mg g−1), while the lowest concentrations occurred in juvenile Arctic cisco (7.5 and 3.6 mg g−1). Multivariate analyses divided all studied fish into five distinct groups with the highest similarity between least cisco and muksun and the highest dissimilarity between juvenile Arctic cisco and Arctic charr. Coregonid fish from the study area had a higher content of docosahexaenoic and eicosapentaenoic acids than their conspecifics from subarctic and temperate habitats. The flesh of the studied fish is a source of a healthy diet for humans. Taking into account that all the studied fish are components of the traditional diet of indigenous peoples in northwestern Siberia, our data may be useful not only for local consumers and anglers but also for stakeholders focused on food policy and food security in the area.